Characterising the role of water in sildenafil citrate by NMR crystallography. Issue 6 (21st January 2016) - Abraham, Anuji; Apperley, David C.; Byard, Stephen J.; Ilott, Andrew J.; Robbins, Andrew J.; Zorin, Vadim; Harris, Robin K.; Hodgkinson, Paul
Abstract : A combination of solid-state NMR techniques, including 13 C/ 1 H correlation, 2 H magic-angle spinning NMR and first principles calculation are employed to characterise the role of water in different hydration states of sildenafil citrate. Abstract : A combination of solid-state NMR techniques, including 13 C/ 1 H correlation, 2 H magic-angle spinning NMR and first principles calculation are employed to characterise the role of water in different hydration states of sildenafil citrate. The 13 C spectrum is fully assigned for the first time and direct correlations made with respect to the crystal structure. 2 H magic-angle spinning NMR is demonstrated to be a powerful tool for the study of dynamic and exchange processes in complex hydrate systems, allowing the behaviour at multiple solvate sites to be characterised without the need for expensive and selective labelling. Use of the 2 H double-quantum frequency allows resolution of the different sites and, consequently, data fitting to determine rates of spin-diffusion between the different sites. The water is shown to be highly dynamic, undergoing C2 rotation, with chemical exchange between different water molecules and also with the host structure. The methods adopted are applicable to the investigation of an extensive range of hydration types found in pharmaceutical drug substances.